Variation in the Utilization of Postoperative Computed Tomography for Patients With Nonsyndromic Craniosynostosis: A National Claims Analysis. (March 2020) - Makar, Katelyn G.; Gunaseelan, Vidhya; Waljee, Jennifer; Vercler, Christian J.; Buchman, Steven R.
Objective: Routine postoperative computed tomography (CT) imaging in nonsyndromic craniosynostosis remains controversial due to the hazards of radiation exposure. The extent to which postoperative head CTs are performed remains unknown. Therefore, we sought to measure the use of postoperative CTs in this population. Design: The authors reviewed insurance claims from OptumInsight, using Current Procedural Terminology codes to identify procedures and postoperative imaging. Multilevel logistic regression was used to describe the odds of undergoing postoperative CTs, adjusting for patient and provider covariates. Participants: Craniosynostosis patients who underwent reconstruction between 2001 and 2017 were reviewed. Patients older than 5 years at surgery, postoperative lengths of stay >15 days, syndromic diagnoses, operative complications within 30 days of surgery, and cranial bone grafting merited exclusion. Main Outcome Measure: Odds of postoperative head CTs after cranial vault reconstruction. Results: In this cohort (n = 1150), 326 (28.4%) patients underwent postoperative head CTs. The number of CTs ranged from 0 to 14. Older age at surgery (odds ratio [OR]: 1.32, P = .002), increasing years of follow-up (OR: 1.12, P < .001), and increasing comorbidities (OR: 1.21, P = .017) were associated with postoperative CTs. After adjusting for patient factors, provider factors accounted for 31.3% of variation in imaging. Conclusions: Over a quarter of patients underwent head CTs following reconstruction, and provider factors accounted for a large percentage of the variation. Given the risks of radiation, neurosurgeons and craniofacial surgeons face a critical need to establish postoperative imaging protocols to reduce unnecessary imaging in these vulnerable patients.